2014
DOI: 10.1038/labinvest.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type bone marrow transplant partially reverses neuroinflammation in progranulin-deficient mice

Abstract: Frontotemporal dementia (FTD) is a neurodegenerative disease with devastating changes in behavioral performance and social function. Mutations in the progranulin gene (GRN) are one of the most common causes of inherited FTD due to reduced progranulin expression or activity, including in brain where it is expressed primarily by neurons and microglia. Thus, efforts aimed at enhancing progranulin levels might be a promising therapeutic strategy. Bone marrow-derived cells are able to engraft in the brain and adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…As in our previous studies, we observed biodistribution via vector integration quantification and transgene expression in the BM and the brain for all treatment groups for LVV.GFP and LVV.GRN (Figures 8A, 8B LVV.GRN-treated groups, we measured supraphysiological levels of human progranulin via ELISA in the plasma and the BM, equivalent to an average of 5-to 11-fold above previously reported wild-type levels (Figures 8C and 8D). 42 We also observed human progranulin levels in whole-brain lysate of LVV.GRN-treated animals, equivalent to 30%-50% of previously reported mouse progranulin levels in the brain (Figure 8G). 43 Using immunohistochemical visualization of mouse and human progranulin, we observed progranulin+ cells in the cortex of LVV.GRN-treated homozygous mutant animals, consistent with the engraftment of LVV.GRN+ cells in the brain (Figure 8I).…”
Section: Hspc-gt In a Model Of Grn-ftd Increases Progranulin And May ...supporting
confidence: 84%
“…As in our previous studies, we observed biodistribution via vector integration quantification and transgene expression in the BM and the brain for all treatment groups for LVV.GFP and LVV.GRN (Figures 8A, 8B LVV.GRN-treated groups, we measured supraphysiological levels of human progranulin via ELISA in the plasma and the BM, equivalent to an average of 5-to 11-fold above previously reported wild-type levels (Figures 8C and 8D). 42 We also observed human progranulin levels in whole-brain lysate of LVV.GRN-treated animals, equivalent to 30%-50% of previously reported mouse progranulin levels in the brain (Figure 8G). 43 Using immunohistochemical visualization of mouse and human progranulin, we observed progranulin+ cells in the cortex of LVV.GRN-treated homozygous mutant animals, consistent with the engraftment of LVV.GRN+ cells in the brain (Figure 8I).…”
Section: Hspc-gt In a Model Of Grn-ftd Increases Progranulin And May ...supporting
confidence: 84%
“…Across all LVV.GRN-treated groups, we measured supraphysiological levels of human progranulin via ELISA in the plasma and the bone marrow, equivalent to an average of 5-11-fold above previously reported wild-type levels (Fig. 8c, d) 42 . We also observed human progranulin levels in whole brain lysate of LVV.GRN-treated animals, equivalent to 30-50% of previously reported mouse progranulin levels in the brain (Fig.…”
Section: Hspc-gt In a Model Of Grn-ftd Increases Progranulin And May Address Lysosomal Dysfunctionmentioning
confidence: 88%
“…Moreover, the symptoms of severe deficiency (CLN11) affect the CNS and retina, where high replacement of dysfunctional GRN-deficient microglia can be achieved. However, a previous study in which mice were conditioned with TBI, BMT showed only partial efficacy, likely due to the low recruitment of hematopoietic cells to the brain 91 . To evaluate the effectiveness of our optimized BU + PLX conditioning, we transplanted a Grn −/− mouse model 92 with either wild-type BM from CAG-GFP mice (Treated, WT BMT) or BM from a Grn −/− mice (Sham, KO BMT) mice.…”
Section: Introductionmentioning
confidence: 84%